Psychometric properties of the Cognitive Functioning Self-Assessment Scale in community-dwelling adults: A cross-sectional online survey - Chung, Krista Ching Wai; Nam, Sujin; Li, Sha; Fan, Heidi Sze Lok; Wong, Janet Yuen Ha; Kwok, Jojo Yan Yan; Davies, Hugh; Huang, Lixi; Annunziata, Maria Antonietta; Fong, Daniel Yee Tak (Frontiers in Psychology, 2023)
Background: The Cognitive Functioning Self-Assessment Scale (CFSS) was developed to allow the self-assessment of perceived cognitive functioning. It has been tested with satisfactory reliability and validity but was not available for the Chinese population. This study aimed to adapt and validate the Chinese version of the CFSS for community-dwelling adults. Methods: A cross-sectional study of a sample of 1,002 Chinese adults from the general population was conducted online (July–August 2022). The Chinese version of the CFSS with 18 items was created through translation, cognitive debriefing, and psychometric evaluation. Exploratory factor analysis (EFA) was performed on the first half of the randomly split sample. A model derived from EFA was confirmed by confirmatory factor analysis (CFA) in the second half of the sample. The model fits were further evaluated with and without subgrouping by age, gender, and education level. Internal consistency was assessed using Cronbach’s alpha () and McDonald’s omega hierarchical coefficients (ωH). Results: EFA (n = 460) revealed a three-factor solution, including spatio-temporal orientation, attention, and memory, which explained 51% of the total variance. The second-order CFA (n = 510) demonstrated a good fit: CFI = 0.951, TLI = 0.944, RMSEA = 0.054, SRMR = 0.040. A second-order multiple-group analysis showed that the structure was invariant by age, gender, and education level. The total CFSS score was significantly associated with the Chinese version of the nine-item Patient Health Questionnaire (r = 0.56, p < 0.001) and the Chinese version of the seven-item General Anxiety Disorder (r = 0.53, p < 0.001). The internal consistency reliability was satisfactory, with = 0.94 and ωH = 0.84. The item-total correlation coefficients ranged from 0.58 to 0.72. Conclusions: The Chinese version of the CFSS possesses good item characteristics, satisfactory validity, and reliability for assessing self-reported cognitive functioning among community-dwelling adults. It is a feasible and appropriate self-assessment instrument to examine cognitive functioning in the Hong Kong Chinese population, which contributes to monitoring and developing strategies to prevent and manage cognitive impairment and disorders for the public’s cognitive health and well-being.